Determination of oxytetracycline residues in the distributed meat products in Tabriz by high-performance liquid chromatography method - Jafar Shadjou; Mohammad Hosein Movassagh (Bihdāsht-i Mavādd-i Ghaz̠āyī, 2023)
The excessive use of antibiotics in animal husbandry has led to the appearance of antibiotic residues in meat and could threaten public health. The study aimed to determine the oxytetracycline residue level in meat products in Tabriz. A total of 60 samples of meat products (sausages, Persian sausages and hamburgers, 20 samples from each meat product) were randomly collected from food supply stores in Tabriz from March to May 2021. High-performance liquid chromatography was used to determine the level of oxytetracycline residue levels in the samples. The results showed that the mean of oxytetracycline residue in sausage, Persian sausage, and hamburger was 82.48±7.06, 57.35±4.27, and 150.79±3.65 µg/Kg, respectively. The mean value of oxytetracycline residues showed a significant (p<0.05) difference between the three products. Also, oxytetracycline residue was observed in all samples. However, in all samples, it was below the allowed limit of Codex Alimentarius (200 µg/kg). The average residue of oxytetracycline in hamburgers was significantly higher than in sausages. In hamburgers with 90% meat, the average amount of oxytetracycline was more than in hamburgers with 70% meat, which can be related to the percentage of meat in the product (p<0.05). Although the level of oxytetracycline residue in the present study was less than the permissible limit, considering the consumption of meat products in the country, it is necessary to control and monitor the presence of antibiotics in foods of animal origin.